2013
DOI: 10.1186/1749-7922-8-45
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy: quality care and cost-effectiveness for today’s economy

Abstract: BackgroundOpen appendectomy (OA) has traditionally been the treatment for acute appendicitis (AA). Beneficial effects of laparoscopic appendectomy (LA) for the treatment of AA are still controversial.AimTo present our technique for LA and to determine whether LA should be the technique of choice of any case of AA instead of OA.Material and methodsAll cases operated for AA (February 2011 through February 2012) by means of LA or OA were prospectively evaluated. Data regarding length of stay, complications, emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
3
24
2
1
Order By: Relevance
“…Most studies opined in favor of LA [1][2][3]4,5,7]. In this study, we found female preponderance and younger age.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Most studies opined in favor of LA [1][2][3]4,5,7]. In this study, we found female preponderance and younger age.…”
Section: Discussionsupporting
confidence: 68%
“…The laparoscopic surgery technique has rapidly spread because of its several advantages over conventional open surgery [1]. The diminishment of postoperative pain and the reduction of length of hospital stay as well as the earlier return to work generated a positive socioeconomic impact [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic appendicectomy is not an innocuous procedure as it can be fraught with dangers if ventured into by an untrained surgeon in the field of laparoscopic surgery 1,[5][6][7][8][9] .Though many studies report a marginal advantage of laparoscopic appendicectomy over the open technique [6][7][8][9] , others opine that it has clear advantages over the open technique [1][2] . Whereas some argue that Laparoscopic appendicectomy (LA) takes more time to perform compared to the open technique, others are of the opinion that once the learning curve is over, the timespent in carrying out LA is similar to that for open appendicectomy 2,[6][7][8][9][10] . Though the period of aneasthesia for LA is often longer than that for open surgery many surgeonsfavour the use of LA because in their experience,these patients had a better quality of life in the immediate post-operative period and thereafter compared to those with open surgery 2,10 .Our index patient gives credence to this assertion because she experienced much less pain compared with those who had been having open appendicectomy and was able to ambulate with minimal discomfort right from the first post-operative day.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some argue that Laparoscopic appendicectomy (LA) takes more time to perform compared to the open technique, others are of the opinion that once the learning curve is over, the timespent in carrying out LA is similar to that for open appendicectomy 2,[6][7][8][9][10] . Though the period of aneasthesia for LA is often longer than that for open surgery many surgeonsfavour the use of LA because in their experience,these patients had a better quality of life in the immediate post-operative period and thereafter compared to those with open surgery 2,10 .Our index patient gives credence to this assertion because she experienced much less pain compared with those who had been having open appendicectomy and was able to ambulate with minimal discomfort right from the first post-operative day. Also,the cosmetic outcome was better (Figure 2), her post-operative morbidity was minimal compared to the open technique and she also had early discharge from the hospital as well as return to normal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, laparoscopic appendectomy has widely become accepted, yet there is controversy over the best method for appendectomy (7,8). Many surgeons have been encouraged to use a variety of incisions for abdominal visceral surgery that are hidden from exposure and have tried to introduce cosmetically better incision for open appendectomy (7,(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%